Diversifying multilingualism: Languages and lects in Amazonia. (August 2021) - Epps, Patience
Purpose: This paper argues for an ethnographically grounded approach to the study of linguistic diversity and multilingualism, taking local ideologies as a starting point for understanding how language varieties emerge and are maintained. It encourages a broad view of multilingualism that includes registers, lects, and other ways in which linguistic and social difference may be aligned and negotiated. Approach: Taking indigenous Amazonia as a case study, we survey evidence for linguistic variants associated with social distinctions that cross-cut many of the divisions conventionally associated with distinct languages, and consider relevant cultural ideologies. Data and Analysis: A range of varieties are considered, including genderlects, whereby men and women use markedly different linguistic forms; variants associated with descent groups and affinal relations; special pet and hunting registers; and shamanic language. Conclusions: Amazonia exhibits a wide range of lects and registers alongside its diversity of languages. These variants are implicated in multilingual practices across the region, and their existence and use are arguably informed by the same ideological framework as that which guides the use of discrete languages. The Amazonian case underscores the importance of casting the net wide in the investigation of small-scale multilingual contexts more generally. Originality: Studies of multilingualism have tended to focus primarily on interactions involving discrete languages, that is, the standard targets of grammars and dictionaries. This contribution brings these other varieties into the conversation, and emphasizes an emic, culturally articulated view of multilingual practice. Significance/Implications: This article illustrates the importance of a broad, ethnographically grounded perspective in the study of small-scale multilingualism, and encourages approaches that consider a range of linguistic variants.